Complex Hegemony and Governmentality. The Politics of Subalterns in Contemporary India - Visentin, Stefano (International Gramsci Journal, 2025)
The article considers the reception in India of Antonio Gramsci’s thought, and in particular the concept of hegemony and passive revolution. In particular, it is the Subaltern Studies research group that has used reference to Gramsci’s work extensively, not only with its founder Ranajit Guha, but also with a second scholar member of the group, Partha Chatterjee. Chatterjee develops, criticizing him in part, Guha's thinking, coining a new definition of “complex hegemony” to apply to the Indian postcolonial state. In an analysis conducted in parallel with economist Kalyan Sanyal, Chatterjee shows how India’s dominant classes seek to enforce a new hegemonic model, which ultimately also employs populist tools, to control and direct the subaltern classes, although the outcomes of this project may never achieve ultimate victory.